SCHOOL MANAGEMENT WITH A FOCUS ON RESULTS: REGULATION AND CONTROL ACTIONS IN PUBLIC SCHOOLS - Fidalgo, Clayse Cardoso; Cerveira, Márcio Brito; Silva, Shirley Maria Dias da; Palheta, Éder do Vale (Seven Editora, 2025)
This study aimed to discuss the impacts of results-based management policies on improving student performance and the quality of education offered, based on a literature review. This review is justified by the interpretation and analysis of a theoretical framework, conducted using the Latin American and Caribbean Health Sciences Literature (LILACS) database and the Scientific Electronic Library Online (SCIELO) virtual library, covering publications from 2015 to 2025. The impacts of results-based management policies on improving student performance and the quality of education offered are of paramount importance because they are based on market logic, employing necessary and appropriate means for the implementation of business management grounded in human capital theory, prioritizing quantitative results over qualitative ones. It is concluded that the results-based management model, through its managerial approach, focuses on developing goals and strategies aimed at achieving results, while also promoting a business model that values ​​only quantitative aspects, prioritizing products and results measured through standardized, large-scale assessments. DOI: https://doi.org/10.56238/sevened2025.038-021